Evaluación de la percepción de estudiantes y docentes de la División Ciencias de la Salud de la Universidad del Norte acerca de las innovaciones en las prácticas en la asignatura Promoción de la Salud y Prevención de la Enfermedad. Barranquilla (Colombia), 2013-2014 - Lecompte-Beltrán, Nelly; Liliana Ríos-García, Ana (Salud Uninorte, 2015)
Objectives: To identify the perception of students and teachers who participated in educational innovation of the Health Promotion and Disease Prevention subject in 2013 and 2014, where students acquire skills for primary health care. Materials and methods: A descriptive evaluation design with a quantitative and qualitative approach which determineted the student satisfaction related to practices, achieving attitudinal goals and skill acquisition. 86 fourth semester students participated, 17 nurses and 69 of medicine from Universidad del Norte at Barranquilla (Colombia). Results: 90% said that practices promoted the development of abilities to work in a community setting, showing respect for the culture of the community; 95% say that in practice the development of an ethical component and communication skills were encouraged. Teachers (85%) believe that there is more teamwork among students and service staff. Conclusions: The perception of satisfaction was consistent for students and teachers under the new rotation model, achieving competence in each work team from the identification of skills in simulation laboratories and performance in actual practice with cases. With innovation the students adquired greater knowledge on the model of care, with emphasis on primary health care. Besides acquiring skills through the laboratory and clinical skills, previous to Community practice.